Derivation of SPH equations in a moving referential coordinate system - Vignjevic, Rade; Campbell, James C.; Jaric, J.; Powell, S. (Elsevier Science B.V., Amsterdam., 2009)
The conventional SPH method uses kernel interpolation to derive the spatial semi-discretisation of the governing equations. These equations, derived using a straight application of the kernel interpolation method, are not used in practice. Instead the equations, commonly used in SPH codes, are heuristically modified to enforce symmetry and local conservation properties. This paper revisits the process of deriving these semi-discrete SPH equations. It is shown that by using the assumption of a moving referential coordinate system and moving control volume, instead of the fixed referential coordinate system and fixed control volume used in the conventional SPH method, a set of new semi- discrete equations can be rigorously derived. The new forms of semi-discrete equations are similar to the SPH equations used in practice. It is shown through numerical examples that the new rigorously derived equations give similar results to those obtained using the conventional SPH equations.
Keywords: SPH; Meshles method; Conservation laws; Moving reference frames; Semi-discretisation